Spatial and seasonal trait selection in dung beetle assemblages along an aridity gradient in the Sahara - Indradatta de Castro‐Arrazola; Francisco Sánchez‐Piñero; Marco Moretti; Joaquín Hortal (Ecology, 2025)
Ecological communities under extreme environments are shaped by a balance of environmental filtering and coexistence mechanisms that result in a series of assembly rules. Although there is abundant evidence about the importance of these community assembly mechanisms in plants, their effects have been seldom compared for animals. We assess their relative importance for the temporal and spatial responses of dung beetle communities along a strong aridity gradient in the edge of the Sahara. Specifically, we study how phylogenetic and functional community structure varies with aridity in space and time and combine it with selected traits to assess the relative importance of mechanisms associated with known assembly rules along the gradient, including whether increasing aridity selects for specific trait values. We surveyed a 400‐km gradient toward the Sahara in the dry and wet seasons of two consecutive years, gathering phylogenetic information and quantifying traits related to aridity from direct measurements and the literature. We calculated metrics of functional and phylogenetic diversity, the decoupled variation in functional diversity, functional and phylogenetic beta diversity, their standardized effect sizes based on null models, and community weighted means for all relevant traits. Then, we assessed the relationships between the spatial and temporal variations in these facets of diversity through linear models, independent principal components analyses, and multiple ANOVAs (MANOVAs). Increasing aridity filters dung beetle communities at the phylogenetic and functional levels, selecting particular trait syndromes in both space and time, as communities change similarly toward the Sahara and between the wet and dry seasons. Contrary to expectations, phylogenetic and functional structure shows a continuous replacement with aridity rather than a nested loss of lineages and trait values, which is not accompanied by a reduction in trait volume along the gradient. Only the hyperarid conditions of the dry season show reductions in trait volume. This implies that responses to aridity lead to assemblages with a common adaptive strategy, dominated by saprophagous species with longer wings and endocoprid behavior, associated with the acquisition of ephemeral resources in the poor desert environment. In addition, animal communities can respond to rapid ecosystem breakdowns if their phenological amplitude includes extreme conditions.